America : with those known parts in that unknowne worlde both people and manner of buildings. - Speed, John, 1552?-1629 (Thomas bassett, 1676)
Map shows geography and settlements in known parts of mid-seventeenth century North America and South America. Includes text, colored illustrations of Native Americans, settlers, and settlements. Inset: [Greenland and Iceland]. California is depicted as an island and the Great Lakes are not shown. Relief shown pictorially. Scale [ca. 1:45,000,000].